Study of Efficacy of Scoring System in Predicting the Clinical Outcome of Diabetic Foot Ulcers - Jesintha Dhas, Achsah; Mathias, Sheldon George; Clara Dsouza, Reshmina Chandni; Arjun, Sanjana P; Ravikar, Joel Deepak (Journal of Neonatal Surgery, 2025)
The burden of DFUs is immense, not only because of the physical toll it takes on patients, but also due to the associated economic costs, which often involve extended hospital stays, surgeries, and rehabilitation Therefore, early detection and effective management of DFUs are crucial to reducing the risk of amputation and improving patient outcomes. However, the challenge lies in identifying the diabetic patients whose foot ulcers are at risk of progressing to amputation and those who can be successfully treated with non-invasive interventions This study aims to assess the efficacy of two relatively newer scoring systems—DUSS (Diabetic Ulcer Severity Score) and SINBAD (Site, Ischemia, Neuropathy, Bacterial infection, Area Depth)—in predicting the clinical outcomes of diabetic foot ulcers. These scoring systems are more comprehensive and take into account a wider range of variables that may influence ulcer healing or the need for amputation. Furthermore, this study compares the efficacy of DUSS and SINBAD with that of Wagner’s Classification and the University of Texas Classification, in order to determine which system provides the most accurate predictions of clinical outcomes. Objective: To assess the efficacy of various foot scoring system for diabetic foot ulcers in predicting the clinical outcome and for prediction of their clinical outcomes Materials And Methods: All patients ( both in and out patients ) , admitted or referred from medical or from any other departments to the SICU and General Surgery Department and its allied sub specialties were included in the study . Results And Observation: In our study Sinbad score the healing probability in score 1 was 100%, score 2 score 2 was 92.11% Score 3 was 72.34%, score 4 was 58.6% healing, score 5 was9.09% and score 6 was 0% healing. In our study according to the Kaplan Meier analysis the probability of healing with duss score -0 was 100%, 84% probability of healing for score 1 while that of score 2 had 19% probability of healing. Patient with DUSS 3 and 4 had 0% probability of healing, DUSS score had a Sensitivity of 98.50% and a specificity of 100.00% to predict amputation . SINDABD score had a Sensitivity of 100.00%and a specificity of 100.00%. DUSS score had a Sensitivity of 98.50% and a specificity of 100.00% to predict amputation . SINDABD score had a Sensitivity of 100.00%and a specificity of 100.00%. Conclusion: The ultimate goal of all the existing classification systems that toward grading the severity of the ulcer. These systems work as a tool for risk stratification and assessment and selection of the proper treatment course, which are crucial in achieving better patient outcomes